2019
DOI: 10.3390/sym11111353
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nanoparticle Enhanced Lubricant Films in Thermal Design of Plain Journal Bearings at High Reynolds Numbers

Abstract: Performance investigation of oil journal bearings is of particular importance given the growing use of them as a support for rotary components in a wide range of industrial machines. Frictional forces and shear stresses, which are proportionate to the velocity of lubricating layers at different points in the bearing space, provide the basis for changing temperature conditions. Various factors such as rotational velocity increase, slip width reduction, and small heat transfer coefficient of lubricant cause inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 31 publications
(35 reference statements)
0
8
0
Order By: Relevance
“…Their results showed that the thermal conductivity of Ag-multi-walled carbon nanotube/water HNFs is higher than that of multi-walled carbon nanotube nanofluids. Jamalabadi et al (2019) performed the impact of nanoparticles on the performance of plain journal bearings using computational fluid dynamics (CFD)-based thermohydrodynamic (THD) numerical simulations. The simulations are conducted in 3 D, incorporating a conjugate HT model for accurate results.…”
Section: Introductionmentioning
confidence: 99%
“…Their results showed that the thermal conductivity of Ag-multi-walled carbon nanotube/water HNFs is higher than that of multi-walled carbon nanotube nanofluids. Jamalabadi et al (2019) performed the impact of nanoparticles on the performance of plain journal bearings using computational fluid dynamics (CFD)-based thermohydrodynamic (THD) numerical simulations. The simulations are conducted in 3 D, incorporating a conjugate HT model for accurate results.…”
Section: Introductionmentioning
confidence: 99%
“…They proposed that fluid containing hybrid nanoparticles prominently interrelate with tumors and accurately delivers drugs to a particular portion of the diseased organ. More suitable studies on the peristaltic flow of nanofluids can be cited in Khan et al (2019), Elelamy et al (2020), Ellahi et al (2019), Moravej et al (2020) and Abdollahzadeh Jamalabadi et al(2019).…”
Section: Introductionmentioning
confidence: 99%
“…The simulation of the microchannel will be very important for designing bio microfluidic devices dealing with rheological complex fluids such as lubricating greases, blood, saliva, or mucus. As mentioned, simulation of multi-phase flow in micro-devices using computational fluid dynamics is needed to use models in which the volume fraction of the fluid is accurately modeled [41,42]. Hence, modeling the interface between multi-phase, especially in very sensitive situations, such as detecting droplet motion and the governing regimes, is very complicated.…”
Section: Introduction To Microstructuresmentioning
confidence: 99%